2009
DOI: 10.1179/136217108x372540
|View full text |Cite
|
Sign up to set email alerts
|

Process forces during friction stir welding of aluminium alloys

Abstract: Flow and consolidation of the material under the tool shoulder and subsequent nugget formation are among the least understood aspects of friction stir welding and processing (FSW/P). Welding parameters and tool profile impact the process forces acting on the tool. This work is an observational study of the process forces associated with bead on plate runs on two aluminium alloys, 6061 and F357. Polar plots of the resultant forces acting on the tool spindle are analysed and correlated to the process parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Those authors reasoned that the highest strength weld corresponded to low angular rotation values of the maximum force and high ratios of maximum-to-minimum force on the tool. Polar plots have also been used [15] to represent resultant force. In that study, tool features were constant, but the spindle speed and travel speed were varied.…”
Section: Introductionmentioning
confidence: 99%
“…Those authors reasoned that the highest strength weld corresponded to low angular rotation values of the maximum force and high ratios of maximum-to-minimum force on the tool. Polar plots have also been used [15] to represent resultant force. In that study, tool features were constant, but the spindle speed and travel speed were varied.…”
Section: Introductionmentioning
confidence: 99%
“…Also, tool runout during processing can affect the magnitude and amplitude of the forces acting on the tool. Balasubramanian et al (2009b) have developed polar plots of the resultant forces acting on the tool spindle during FSW/P of cast and wrought aluminum alloys and analyzed the effect of process forces when there were no voids. For nuggets without any voids/channels, the resultant force acts in the region between the trailing edge and advancing side.…”
Section: Force Signaturementioning
confidence: 99%
“…Hattingh et al (2008) have analyzed the force foot prints to study the influence of tool geometry on FSW process parameters and on weld tensile strength and thereby optimize the tool design to produce welds with 97% of the parent plate tensile strength in Al 5083-H321 alloy. Balasubramanian et al (2009b) have investigated the effect of process forces during FSP of cast and wrought aluminum alloys. Polar plots of the net resultant forces acting on the tool during processing were used to understand the presence or absence of defects in the nugget region.…”
Section: Introductionmentioning
confidence: 99%
“…For repairs on site, the miniaturization of the FSW equipment has been desired. Balasubramanian et al experimentally demonstrated that the forces acting on the tool spindle vary with the processing parameters 4,5) . Blignault et al developed the multi axial transducer for measuring the process force footprint 6) .…”
Section: Introductionmentioning
confidence: 99%